Challenges and status of tuning simulations for CLIC traditional beam delivery system - Bodenstein, R; Burrows, P; Marin, E (JACoW Publishing, 2018)
The beam delivery system (BDS) for the 3 TeV version of the Compact Linear Collider (CLIC) has two main design types. One type is referred to as the local scheme, as it is approximately one kilometer shorter and corrects the chromaticity in both planes. The other type is referred to as the traditional scheme, and separates the chromaticity correction of each plane into different areas. The expectation early in the studies is that the traditional scheme would be easier to tune. However, it appears that this is not the case. Previous proceedings have shown the complications in tuning the traditional scheme. This work will address the problems experienced in tuning simulations for the traditional BDS and describe the current state of these simulation.